PENDIDIKAN NASIONAL DAN TANTANGAN GLOBALISASI: Kajian kritis terhadap pemikiran A. Malik Fajar - Rusniati Rusniati (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2015)
The globalization era which is full of challenges couldnot be avoided. Therefore, the educational institutions, especially islamic education, should be able to answer those challenges in order to change the direction of educational orientation. One of figures who is serious in building educational thinking paradigm is A. Malik Fadjar. This study aims to explore his educational thinking paradigm and educational concept proposed. A. Malik Fadjar faces the challenge of global era. The result of study showed that his educational thinking paradigm is holistic; in which the education is humanists, liberative, integralistics, multicultural and futuristic, either in the aspect of vision and mision, institution, management, patterns of educational interaction, curriculum, and educator. To face global era, A Malik Fadjar states that there are three big challenges, they are to protect the result achieved, anticipate the global era, and do some changes and adjustment of the national education system.